Geopolitik Kritis Dalam Konteks Keamanan Maritim: Studi Kasus Pemberontak Houthi Di Laut Merah - Dao, Yunias; Yusnaldi Yusnaldi; Kusuma Kusuma (DEFENDONESIA, 2025)
This research examines the impact of the Houthi rebellion on maritime security in the Red Sea, a critical corridor for global trade. The background of the research highlights the importance of the Red Sea as a vital trade route between Asia, Europe and Africa, and the security challenges posed by the activities of the Houthi rebels, who often target commercial vessels and maritime infrastructure. The purpose of this research is to analyze how Houthi activities affect maritime security and regional and global geopolitical dynamics, and to recommend response mechanisms that can strengthen stability and security in the Red Sea. The research methodology uses a qualitative approach with a case study, where data was collected through literature review and analyzed using content analysis to identify themes, patterns, and relationships in the data. The findings show that Houthi activities have disrupted trade routes, increased the risk of military confrontation, and affected regional and global stability. The study's conclusions underscore the importance of a more coordinated and multilateral approach to addressing the challenges posed by the Houthis, including increased maritime patrols, active diplomacy, and local capacity building. Strategic recommendations include joint patrols, inclusive political dialogue, and the development of strong international legal tools to protect shipping lanes and reduce security incidents.